Evaluating the user experience of online transportation applications with the UEQ approach to people's lifestyles - Amran, Ali; Putri, Yogi Arditya Candani; Susmawati, Putri Rahayu; Aulita, Rida Nur; Astutik, Astutik; Fitria, Yaumul (Jurnal Mandiri IT, 2024)
This study was conducted to evaluate the user experience of online transportation applications using a user experience questionnaire aimed at the society lifestyle. The study makes reference to the following user evaluations: novelty, attractiveness, clarity, efficiency, and stimulation. This kind of study is known as quantitative research, and it looks at the issue of user experience in relation to society's lifestyle. data gathering through the distribution of questionnaires. Tables and graphs are used to display the descriptive analysis and presentation of the data. The lifestyle variable was positively and significantly impacted by the user experience variable, according to the results. As a result, the proprietor of the online transportation program has the ability to modify its features.